Laminated Wood Beams Reinforced with Glass Fiber Polymer - Hayiyusoh, Imron; Mangsamong, Wannachaporn; Kodae, Hasun (Princess of Naradhiwas University Journal, 2019)
Laminated wood is one of the most popular materials and is widely accepted in terms of structural member and non-structural member. Rubber wood beams could not directly use as structural member. Then, the rubber wood reinforcing with polymer materials and laminated wood beams can use as a structural member, however, these materials were used in a limit. There were little involved research and not enough to evaluate the behavior and ability of the structural strength capacity. This research presented assessment the structural load behavior and bending strength capacity properties of beams with different reinforcement of glass fiber and polymers, The fiber stress at proportional point, modulus of rupture, apparent modulus of elasticity, and maximum shear stress were tested to evaluate the maximum moment capacity. The results were analyzed to understanding the behavior of evaluating weight performance.